Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1002/art.40504
|View full text |Cite
|
Sign up to set email alerts
|

Review: Synovial Cell Metabolism and Chronic Inflammation in Rheumatoid Arthritis

Abstract: Metabolomic studies of body fluids show that immune-mediated inflammatory diseases such as rheumatoid arthritis (RA) are associated with metabolic disruption. This is likely to reflect the increased bioenergetic and biosynthetic demands of sustained inflammation and changes in nutrient and oxygen availability in damaged tissue. The synovial membrane lining layer is the principal site of inflammation in RA. Here, the resident cells are fibroblast-like synoviocytes (FLS) and synovial tissue macrophages, which ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
203
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 236 publications
(211 citation statements)
references
References 106 publications
5
203
0
3
Order By: Relevance
“…Macrophages, known as the classically activated pro‐inflammatory M1 phenotype and the alternatively activated anti‐inflammatory M2 phenotype, play a major role in joint inflammation and subsequent tissue damage in RA . To verify the effect of CB2 on macrophage polarization during the inflammation of CIA, we performed double immunostaining of F4/80 and iNOS or CD206.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Macrophages, known as the classically activated pro‐inflammatory M1 phenotype and the alternatively activated anti‐inflammatory M2 phenotype, play a major role in joint inflammation and subsequent tissue damage in RA . To verify the effect of CB2 on macrophage polarization during the inflammation of CIA, we performed double immunostaining of F4/80 and iNOS or CD206.…”
Section: Resultsmentioning
confidence: 99%
“…The activation of CB2 inhibits the inflammatory response in the CIA mice by switching M1 macrophages to M2 macrophages. Macrophages are considered to serve essential functions in RA pathogenesis because they are the main producers of pro‐inflammatory cytokines that promote inflammation . The number of synovial macrophages is correlated with the clinical disease activity, and selective macrophage depletion has a strong anti‐inflammatory effect in animal models of arthritis .…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating data have proven that FLS are crucial in the development of RA. The dysregulated proliferation, as well as highly invasive and migratory abilities of FLS in RA joints are the main hallmarks of RA (Doody et al, ; Falconer et al, ). Activated FLS can produce several pro‐inflammatory cytokines and MMPs, which play pivotal roles in the development of RA (Doody et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Further studies revealed that these processes were linked to PC substrates blockade such as Notch receptor [9]. Furthermore, following inflammatory stimulus, the latter interacts first with cell surface through the proteoglycan layer that includes different classes of adhesion molecules directly connected the ECM [2]. The adhesion capacity and/or the expression of these adhesion molecules are also regulated by the PCs, suggesting the direct participation of the PCs in the initial and late interaction of targeted cells with pathogenic stimulus.…”
Section: Proprotein Convertases In Intercellular Communication Leadinmentioning
confidence: 99%
“…Indeed, inflammation is linked to increased activation and migration/ invasion of circulating immune cells including lymphocytes and macrophages that release inflammatory mediators (cytokines and cyclooxygenase derivatives). The persistent accumulation of these mediators causes various pathologies including obesity, rheumatoid arthritis, diabetes, cardiovascular disease, inflammatory bowel syndrome and cancer [1][2][3].…”
Section: Inflammation and Neoplasiamentioning
confidence: 99%